Bioavailability of a Capsaicin Lipid Multi-particulate Formulation in Rats (Jul, 10.1007/s13318-021-00697-x, 2021) - Şahin, Kazım; Küçük, Ömersman; Orhan, Cemal; Sahin, Emre; Fowler, Kelli; White, Tyler; Bellamine, Aouatef (Springer France, 2021)
[Abstract Not Available]